Pengaruh Disiplin, Konflik Kerja Dan Stres Kerja Terhadap Kinerja Karyawan Pada PT. Sukses Usaha Nirwana - Ina Namora; Windy; Sharon; Stephani (Jurnal Manajemen Bisnis Eka Prasetya, 2020)
The researcher took the object of research from PT Sukses Usaha Nirawana. Decline in employee performance can be seen from observations of sales data that occurred during the year are not able to reach the targets set. Some factors of performance decline are thought to be caused by discipline, work conflict and work stress. Low work discipline makes employees often do not work with the rules set by the company. From the data it can be seen that the provision of different basic salaries and bonuses is received by employees and not in accordance with the length of service given to employees differing from one position with the same division. Conflicts that occur between one division with a division or with other divisions will create difficulties because there are no good solutions to problems by employees. Employees who are less motivated at work can also cause work stress that has an impact on the employee's performance. This study uses a saturated sampling technique. A total population of 63 people and 30 people were taken from the Medan Center Point Fishermen's Office for validity testing. Theories used to support research are theories of human resource management related to discipline, work conflict and work stress and performance. The research method used is a quantitative approach to the type of quantitative descriptive research. Methods of data collection by interview, distribution of questionnaires and study of documentation. The analytical method used is multiple linear regression. The results showed that discipline, work conflict and work stress simultaneously and partially had a significant positive effect on employee performance with a coefficient of determination.